PENGEMBANGAN PARIWISATA HALAL THAILAND DALAM KERJASAMA INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) 2017-2021 - Putri, Siti Annisa Shafina; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Thailand is a non-Muslim country that has succeeded in developing the halal tourism sector through the Indonesia-Malaysia-Thailand (IMT-GT) cooperation so that the purpose of this study is to find out how the development of Thai Halal Tourism in the Indonesia-Malaysia-Thailand (IM-GT) cooperation including its successes and challenges. In addition, it looks at the impact of economic sector growth by Thailand's Halal Tourism Development in the collaboration. In this research, the author uses an approach through the theory of International Cooperation by K.J, Holsti which is a strong foundation in forming effective and sustainable cooperation for IMT-GT, the perspective of Neo-liberalism Institutionalism and the level of nation-state analysis in analyzing and understanding events based on existing data. The author uses qualitative research methods, secondary data collection techniques obtained through literature studies obtained from various literatures. Thailand is a country with a majority non-Muslim population that has successfully developed the halal tourism sector through various policies, strategies and collaboration in IMT-GT cooperation. Thailand's national policies are adjusted to the IMT-GT cooperation targets which include accepting halal standards, increasing the number of technical experts and professionals in the halal field, developing export-oriented halal SMEs, increasing halal producers and service providers, and providing better access. Keywords: Halal Tourism, Indonesia-Malaysia-Thailand Growth Triangle, Cooperation, International Organization